(untitled) (Acta Judicial Journal, 2022)
This paper analyses the fundamental right of data protection regarding its treatment by the criminal court, as the authority responsible for the processing of data for the purposes of investigation and prosecution of crimes. The main procedural implications deriving from its effective application will also be analyzed.